Evaluation of oxidative stability of mayonnaise containing poly ε- caprolactone nanoparticles loaded with thyme essential oil - Rhaysa Beatriz dos Passos; Giovana Carolina Bazzo; Aline da Rosa Almeida; Carolina Montanheiro Noronha; Pedro Luiz Manique Barreto
Suspensions of poly ε-caprolactone (PCL) nanoparticles loaded with thyme essential oil were prepared as a natural antioxidant in mayonnaise. Mean particle size was 204.9 ± 2.7 and 240.0 ± 5.5 nm respectively for nanoparticles prepared with PCL alone (NP-C) and for those loaded with thyme essential oil (NP-T). The polydispersity index indicated a homogeneous distribution of all particles, with no significant difference between NP-C and NP-T samples. The nanoparticles showed a large negative charge evidenced by zeta potential rates, indicating high physical stability. The use of PCL as a polymer provided high encapsulation efficiency for thyme essential oil (91.15 ± 2.12 %). DPPH (2,2-diphenyl-1-picrylhydrazyl) method determined IC50 rates were 476.4 ± 33.6 and 483.5 ± 20.4 µg mL-1respectively for unencapsulated oil and for NP-T, evidencing pronounced antioxidant activity. NP-C, NP-T and synthetic antioxidant butylhydroxytoluene (BHT) were applied to samples of mayonnaise and their oxidative stability evaluated for eight days in an oven at 63 ± 3ºC. Results of hydroperoxide value (HP) and thiobarbituric acid reactive substances (TBARS) showed that NP-T had a similar performance as synthetic antioxidant BHT in the prevention of mayonnaise lipid oxidation.